Is observation mathematically-laden? - Thomas Mueller (Principia: An International Journal of Epistemology)
In this article, we will defend an epistemological claim: that observation is mathematically-laden. A well-known thesis in the philosophy of science is that observation is theory-laden.  The claim that observation is mathematically laden can be partially seen as an analogous argument.